2023
DOI: 10.1111/een.13245
|View full text |Cite
|
Sign up to set email alerts
|

Adult monarch butterflies show high tolerance to neonicotinoid insecticides

Abstract: Numerous studies have documented the negative effects of neonicotinoids on bees; it remains crucial to examine how neonicotinoids affect other non‐target nectar‐feeding insects, such as the monarch butterfly, Danaus plexippus. Wildflowers growing near agricultural areas can be contaminated with neonicotinoids that affect survival or cause sublethal changes to behaviours of nectar‐feeding insects. Nectar residues of imidacloprid and clothianidin found in milkweeds and wildflowers adjacent to agricultural field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 91 publications
(129 reference statements)
0
4
0
Order By: Relevance
“…This result does not align with the relationship between neonicotinoids and monarch mortality in lab toxicology studies; indeed these lab studies show that neonicotinoids are among the least toxic agents[77]. Further, field-relevant exposure levels are estimated to be well below those expected to cause monarch mortality based on laboratory toxicology studies[85,86].…”
Section: Discussionmentioning
confidence: 97%
“…This result does not align with the relationship between neonicotinoids and monarch mortality in lab toxicology studies; indeed these lab studies show that neonicotinoids are among the least toxic agents[77]. Further, field-relevant exposure levels are estimated to be well below those expected to cause monarch mortality based on laboratory toxicology studies[85,86].…”
Section: Discussionmentioning
confidence: 97%
“…This result does not align with the relationship between neonicotinoids and monarch mortality in lab toxicology studies; indeed these lab studies show that neonicotinoids are among the least toxic agents [ 77 ]. Further, field-relevant exposure levels are estimated to be well below those expected to cause monarch mortality based on laboratory toxicology studies [ 85 , 86 ]. Yet, the prophylactic use of neonicotinoids means that there is far more opportunity for buildup in the environment, and the true environmental distribution is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontaminated 30% honey water sponges were also supplied as food, and monarchs may have fed less on or avoided the neonicotinoid-contaminated flowers. More recently, Prouty et al [45] concluded that adult monarchs show high tolerance to field-realistic levels of neonicotinoid insecticides. However, these authors held monarchs for only 10 days during exposure to imidacloprid, which is insufficient to show an impact on medium-to long-term survival, judging from the results of James [44].…”
Section: Neonicotinoids As the Potential Primary Driver Of The Wester...mentioning
confidence: 99%
“…If laboratory insecticide bioassays are to reflect real-world scenarios, then materials used in the field should be tested. Thus, commercially formulated insecticide products [44] rather than active ingredients [30,31,45] should be used. Commercial formulations of insecticides have invariably proven to be more toxic than active ingredients alone [46][47][48].…”
Section: Neonicotinoids As the Potential Primary Driver Of The Wester...mentioning
confidence: 99%